2001
DOI: 10.1002/em.1037
|View full text |Cite
|
Sign up to set email alerts
|

Gender difference in DNA adduct levels among nonsmoking lung cancer patients

Abstract: Lung cancer is the leading cause of cancer mortality in Taiwanese women. Cigarette smoking cannot explain the high lung cancer mortality in this population because less than 10% of women in Taiwan are smokers. Therefore, environmental factors other than smoking may play an important role in lung cancer development in female nonsmokers. The purpose of this study was to elucidate the role of environmental carcinogen exposure in lung cancer development in Taiwanese female nonsmokers, based on DNA adduct formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 28 publications
(35 reference statements)
1
30
0
1
Order By: Relevance
“…We divided our cases into four groups based on sex and smoking status: 420 female never-smoker cases, 140 female ever-smoker cases, 130 male never-smoker cases, and 788 male ever-smoker cases. In females, never smokers had 119 mutations in exon 19, 100 in exon 21,8 The EGFR mutation spectrum of the total group, East Asia, and the United States and Australia cases stratified by histologic subtypes are shown in Table 2 and Supplementary Material 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We divided our cases into four groups based on sex and smoking status: 420 female never-smoker cases, 140 female ever-smoker cases, 130 male never-smoker cases, and 788 male ever-smoker cases. In females, never smokers had 119 mutations in exon 19, 100 in exon 21,8 The EGFR mutation spectrum of the total group, East Asia, and the United States and Australia cases stratified by histologic subtypes are shown in Table 2 and Supplementary Material 1.…”
Section: Resultsmentioning
confidence: 99%
“…Previous molecular data indicate that cancers arising in women smokers harbored significantly more tobacco-related p53 mutations, G:C to T:A transversions, than those in male smokers (20). Furthermore, DNA adduct levels of benzo(a)pyrene diol epoxide (a tobacco carcinogen) in females with lung cancer were markedly greater than those arising in males, suggesting sex differences in susceptibility to DNA damage derived from environmental carcinogen exposure (21). Of note, there was no specific association between smoking status and the type of point mutation (transversion and transition) in EGFR mainly because that majority of point mutation is G to T transversion at the second letter of codon 858.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been shown that females are more susceptible to environmental carcinogens because DNA mutations were more frequently found in never-smoking female than never-smoking male lung cancer patients. 22 Moreover, it has been shown that females have a lower capacity of DNA repair than males, which is suggested to be the result of epigenetic and genetic effects of genes related to metabolic detoxification and DNA repair pathways. 23 Thus, sex-related difference in mutagenesis may be explained by the interplay between genes and the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of DNA adducts in lung cancer patients have indicated higher adduct levels in lung tissue of cancer cases (Cheng et al, 2000b(Cheng et al, , 2001) and in their peripheral white blood cells (Vulimiri et al, 2000;Perera et al, 1989) compared with controls. Higher adduct levels were reported in lung tissue from women compared with men (Cheng et al, 2001).…”
Section: Dna Adducts Associated With Lung Cancermentioning
confidence: 99%
“…Higher adduct levels were reported in lung tissue from women compared with men (Cheng et al, 2001). In a prospective study, researchers reported that increased adduct levels in white blood cells were associated with lung cancer risk among those who were current smokers at the time of blood sampling (Tang et al, 2001).…”
Section: Dna Adducts Associated With Lung Cancermentioning
confidence: 99%